2019
DOI: 10.1186/s13229-019-0276-2
|View full text |Cite
|
Sign up to set email alerts
|

Visual attention to faces in children with autism spectrum disorder: are there sex differences?

Abstract: Background: The male bias in autism spectrum disorder (ASD) diagnoses is well documented. As a result, less is known about the female ASD phenotype. Recent research suggests that conclusions drawn from predominantly male samples may not accurately capture female behavior. In this study, we explore potential sex differences in attention to social stimuli, which is generally reported to be diminished in ASD. Population-based sex differences in attention to faces have been reported, such that typically developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
56
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 58 publications
9
56
1
1
Order By: Relevance
“…First, unlike age, sex did not significantly contribute to any of the linear mixed-effects models, suggesting that while it may be important to account for this variable as a covariate [ 53 ], there is little evidence within the current study to suggest that patterns of social attention are influenced by sex. This finding is consistent with several studies that have not identified sex differences in behavioral features of ASD [ 54 ], but is in contrast to one study that identified sex differences in visual attention to dynamic social scenes for children with ASD [ 55 ]. Methodological differences between our study and Harrop et al [ 55 ] could reconcile this discrepancy as the study included a younger, more restricted age range of participants between 6 and 10 years.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…First, unlike age, sex did not significantly contribute to any of the linear mixed-effects models, suggesting that while it may be important to account for this variable as a covariate [ 53 ], there is little evidence within the current study to suggest that patterns of social attention are influenced by sex. This finding is consistent with several studies that have not identified sex differences in behavioral features of ASD [ 54 ], but is in contrast to one study that identified sex differences in visual attention to dynamic social scenes for children with ASD [ 55 ]. Methodological differences between our study and Harrop et al [ 55 ] could reconcile this discrepancy as the study included a younger, more restricted age range of participants between 6 and 10 years.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with several studies that have not identified sex differences in behavioral features of ASD [ 54 ], but is in contrast to one study that identified sex differences in visual attention to dynamic social scenes for children with ASD [ 55 ]. Methodological differences between our study and Harrop et al [ 55 ] could reconcile this discrepancy as the study included a younger, more restricted age range of participants between 6 and 10 years. It is possible that sex differences in social attention are developmentally sensitive, and that combining children, adolescents, and adults together may mask some developmental trends, and our sample size of 29 females compared to a larger proportion of males was not sufficient to detect any differences.…”
Section: Discussionsupporting
confidence: 92%
“…ADOS-2 calibrated severity scores of 1-2 indicate minimal-to-no evidence of autism symptoms, scores of 3-4 indicate a low level of autism symptoms, 5-7 a moderate level, and 8-10 a high level. The Social Communication Questionnaire (SCQ) [67] "Lifetime" version [73] was filled out by parents to assess the presence of ASD symptoms. To assess cognition, clinicians administered one of four cognitive tests; scores were standardized by J. Pandey and reduced to a single cognitive estimate, along with verbal and nonverbal subscores (see S2 for further details).…”
Section: Methodsmentioning
confidence: 99%
“…A primary limitation of the current study is the absence of girls with ASD among our participants, as girls and women with ASD are underrepresented in the literature [Lai, Baron‐Cohen, & Buxbaum, 2015], may be incompletely characterized by current diagnostic practices [e.g., Boorse et al, 2019; Dworzynski, Ronald, Bolton, & Happé, 2012], may demonstrate distinct patterns of social information processing [Harrop et al, 2018; Harrop et al, 2019], and may have different social experiences and trajectories in comparison to males with ASD [Lai & Szatmari, 2020]. These differences may be especially prominent in a sample such as this one, in which participants had strong verbal and nonverbal cognitive skills [Dworzynski et al, 2012].…”
Section: Discussionmentioning
confidence: 99%